Analysis of the levels of hope and influencing factors in infertile women with first-time and repeated IVF-ET cycles - Ying Ni; Limin Huang; Chenye Tong; Wen Qian; Qiong Fang (BMC, 2021)
Plain language summary Hope level is closely related to patients' mental health and emotional state. Therefore, improving the hope level of infertile women with IVF-ET could contribute to relieving the psychological pressure of patients and improving the success rate of pregnancy. This study aimed to evaluate the hope level of infertile women with different IVF-ET cycles and analyse its influencing factors to provide guidance for clinical nurses to clarify the intervention objects, select reasonable intervention measures and improve the hope levels of patients. A total of 298 IVF-ET patients were recruited in the study, including 150 in the first-time cycle group and 148 in the repeated cycle group. The results showed that the hope level of patients with repeated IVF-ET cycles was significantly lower than that of patients undergoing first-time treatment. We also analysed its influencing factors and found that repeated IVF-ET cycles and age were independent negative correlation factors in hope levels. High monthly income, living in the city, high marital adjustment and social support score were independent positive correlation factors in hope levels. Therefore, maintaining a good marriage adjustment and establishing a good social support and relationship network could effectively improve their hope levels.